Heightened Attention to Medical Privacy: Challenges for Unbiased Sample Recruitment and a Possible Solution - Nattinger, Ann B. (Oxford University Press, 2010)
Subject recruitment for epidemiologic studies is associated with major challenges due to privacy laws now common in many countries. Privacy policies regarding recruitment methods vary tremendously across institutions, partly because of a paucity of information about what methods are acceptable to potential subjects. The authors report the utility of an opt-out method without prior physician notification for recruiting community-dwelling US women aged 65 years or older with incident breast cancer in 2003. Participants (n = 3,083) and possibly eligible nonparticipants (n = 2,664) were compared using characteristics derived from billing claims. Participation for persons with traceable contact information was 70% initially (2005–2006) and remained over 90% for 3 follow-up surveys (2006–2008). Older subjects and those living in New York State were less likely to participate, but participation did not differ on the basis of socioeconomic status, race/ethnicity, underlying health, or type of cancer treatment. Few privacy concerns were raised by potential subjects, and no complaints were lodged. Using opt-out methods without prior physician notification, a population-based cohort of older breast cancer subjects was successfully recruited. This strategy may be applicable to population-based studies of other diseases and is relevant to privacy boards making decisions about recruitment strategies acceptable to the public.